MAKNA BUDAYA DALAM LIRIK-LIRIK LAGU DAERAH MINAHASA SEBAGAI KEARIFAN LOKAL (CULTURAL MEANING IN MINAHASAN TRADITIONAL SONGS LYRICS AS A LOCAL WISDOM) - Stephani Johana Sigarlaki (Balai Bahasa Sulawesi Utara, 2016)
“Cultural Meaning in the Lyrics of Minahasa Folk Songs as Local Wisdom” is a result of study that was conducted to get cultural meaning in the lyrics of Minahasan folk songs. The problems of the study are 1) what vocabularies, phrases, clauses, and sentences that can be found in the lyrics of Minahasan folk songs that songs that show local wisdom in Minahasa and 2) what cultural meaning that bore in the lyrics of Minahasan songs.The research is aimed to indentify and classify vocabularies, phrases, clauses, and sentences found in the lyrics of Minahasan folk songs that show local wisdom in Minahasa and 2) explain cultural meaning that bore in the lyrics ofMinahasan folk songs. The methods of research that is applied is qualitative descriptive method through the stages of data collecting and analyzing. The data was gathered by technique of observation and interview that then analyzed bysemiotics theory of Pierce and Rifaterre. The result of this research is an explanation on cultural meaning that is bored in the lyrics of Minahasan folk song, such as words, phrases, and sentences as local wisdom.